Anticoagulation with Argatroban in a Patient with Heparin-Induced Thrombocytopenia and Renal Insufficiency Undergoing Orthotopic Heart Transplantation - Michael Stuart Green; Johann Mathew; Christopher Ryan Hoffman; Henry Liu (Case Reports in Anesthesiology)
Unfractionated heparin is the anticoagulant of choice for cardiac surgery that requires cardiopulmonary bypass. However, it can cause serious side effects like heparin-induced thrombocytopenia (HIT), an immune-mediated process where antibodies are directed against heparin and platelet 4 complexes. In such cases, alternative pharmacologic strategies are implemented to facilitate safe bypass conditions. A woman with severe decompensated heart failure was heparinized for intra-aortic balloon pump and subsequent LVAD placement. On day 6, a fall in platelets from 113,000 to 26,000 was noted. She was diagnosed with HIT. Heparin was discontinued and replaced with an argatroban infusion for the duration of her care until heart transplantation was completed. We review the mechanism, diagnosis, and complications of HIT. We discuss cardiopulmonary bypass and its relation to heparin, HIT, and heparin alternatives. We discuss argatroban’s relevant pharmacology, clinical use, advantages, and disadvantages.